Epigramy żałobne Klemensa Janickiego (1516–1543) - Lewandowski, Ignacy (Wydawnictwo Naukowe Uniwersytetu im. Adama Mickiewicza, 2008)
In the paper above 20 funeral epigrams by Klemens Janicki were investigated. The author of the paper focussed his attention on the richness of topics, egregious and their ancient and recent examples.
Funeral epigrams of Klemens Janicki (1516–1543)
Keywords: Klemens Janicki; funeral epigrams